Genetic analysis of grapevine root system architecture and loci associated gene networks - Alahakoon, Dilmini; Fennell, Anne (Frontiers in Plant Science, 2023)
Own-rooted grapevines and grapevine rootstocks are vegetatively propagated from cuttings and have an adventitious root system. Unraveling the genetic underpinnings of the adventitious root system architecture (RSA) is important for improving own-rooted and grafted grapevine sustainability for a changing climate. Grapevine RSA genetic analysis was conducted in an V. sp. ’VRS-F2‘population. Nine root morphology, three total root system morphology, and two biomass traits that contribute to root anchorage and water and nutrient uptake were phenotyped. Quantitative trait loci analysis (QTL) was performed using a high-density integrated GBS and rhAmpSeq genetic map. Thirty-one QTL were detected for eleven of the RSA traits (surface area, root volume, total root length, fresh weight, number of tips, forks or links, longest root and average root diameter, link length, and link surface area) revealing many small effects. Several QTL were co-located on chromosomes 1, 9, 13, 18, and 19. QTL with identical peak positions on chromosomes 1 or 13 were enriched for ALFIN-LIKE, AP2-EREBP, AS2, C2C2-CO, HMG, and MYB transcription factors, and QTL on chromosomes 9 or 13 were enriched for the regulation of autophagy pathway. QTL modeling for individual root traits identified eight models explaining 13.2 to 31.8% of the phenotypic variation. ‘Seyval blanc’ was the grandparent contributing to the allele morphology models that included a greater surface area, total root length, and branching (the number of forks and links) traits promoting a greater root density. In contrast, the V. riparia ‘Manitoba 37’ contributed the allele for greater average branch length (link length) and diameter, promoting a less dense elongated root system with thicker roots. LATERAL ORGAN BOUNDARY DOMAIN (LBD or AS2/LOB)) and the PROTODERMAL FACTOR (PFD2 AND ANL2) were identified as important candidate genes in the enriched pathways underlying the hotspots for grapevine adventitious RSA. In addition, cell cycle and circadian rhythm pathways were enriched in the modeled root traits (total root length and the number of tips, forks, and links). These loci and underlying enriched pathways and candidate genes provide a profile of the genetic regulation of adventitious root development and identify candidate genes for further exploration in grapevine root system improvement.